PENGARUH IKLAN DAN KEMASAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK MIE SEDAAP INSTANT DI GIANT PLAJU PALEMBANG - Sopian . (Fakultas Ekonomi Universitas Tridinanti Palembang, 2019)
ABSTRACT Advertising is one form of promotion that is most widely used by companies in promoting their products. Packaging is the activity of designing and producing containers or packaging of a product. Purchasing decisions are a person's buying behaviour in determining a product choice to achieve satisfaction according to the needs and desires of consumers which include problem recognition, information seeking, evaluation of purchasing alternatives, purchasing decisions, and behaviour after purchase. The objectives discussed in this study were to find out the simultaneous and partial effects of advertising and packaging on the purchasing decisions of Mie Sedaap Instant products at Giant Plaju Palembang. The population in this study were all consumers using Mie Sedaap Instant products at Giant Plaju Palembang. The sample technique used in accidental sampling. The samples in this study were 50 consumers who bought Mie Sedaap Instant products at Giant Plaju Palembang. The analytical method used in Multiple Linear Regressions. The results of the study explain the effect simultaneously (F test) shows that the variable Ad (X1) and Packaging (X2) jointly influence the Purchase Decision (Y) with a calculated Fcount (68,827) > Ftable (3,195) so that the alternative hypothesis is accepted and null hypothesis rejected. The results of the partial effect (t test) Ad variables (X1) have a significant effect on Purchasing Decisions (Y) with a tcount (4.083) > ttable (1,678), so the alternative hypothesis is accepted and the null hypothesis is rejected. Packaging variables (X2) have a significant effect on Purchasing Decisions (Y) with a value of tcount (6.656) > ttable (1,678) so the alternative hypothesis is accepted and the null hypothesis is rejected. Keywords : Advertising, Time, and Purchasing Decisions